Factors that lead to adoption of E-commerce among youths in Kuala Lumpur / Adam Aziz Muhamed Nasir - Muhamed Nasir, Adam Aziz (Faculty of Business and Management, 2015)
The purpose of this study is to investigate the relationship between three independent variables against one dependent variable. Basically, it consists of three factors influencing the adoption of e-commerce among youths in Kuala Lumpur and the factors are Trust in Sellers, Perceived Risks and Frauds and Perceived Behavioural Control. In order to complete this write up, a few hypotheses were constructed and focused on the objectives to determine whether there were significant relationships between Trust in Sellers, Perceived Risks and Frauds and Perceived Behavioural Control against Adoption of E-commerce. For this study, 384 youths residing in Kuala Lumpur were chosen as respondents for this study. However, only 279 responses were returned back to the researcher. The data was obtained from primary data by using questionnaires. All data collected through the questionnaires were analyzed systematically by Statistical Package for Social Science (SPSS). From the correlation testing, the result shows three independent variables which are Trust in Sellers and Perceived Behavioural Control have strong relationships, while Perceived Risks and Frauds has moderate relationship. For multiple regression analysis, the results indicate that Trust in Sellers, Perceived Risks and Frauds and Perceived Behavioural Control are factors that lead to Adoption of E-commerce among youths in Kuala Lumpur. In terms of hypotheses testing, two hypotheses pertaining to Trust in Sellers and Perceived Behavioural Control are accepted, while hypothesis concerning Perceived Risks and Frauds is rejected.